The Institute of Complementary Physics - Gariboldi, Leonardo (Springer, 2022)
The Institute of Complementary Physics (1924–28) was the first institution of physics research of Milan University. The institute was a subdivision of the highly fragmented Faculty of Sciences, established in 1924 with the foundation of Milan University thanks to Luigi Mangiagalli’s willingness to have in Milan a public university complete with the four faculties of literatures and philosophy, medicine and surgery, law, and sciences. The director of the Institute of Complementary Physics was Aldo Pontremoli, a young scientist from the Rome school of physics who also trained at the Cavendish Laboratory in Cambridge. He was the winner, with Enrico Fermi and Enrico Persico, of the first public competition for a chair of Theoretical Physics in Italy. Pontremoli quickly established a modern institute with a laboratory of radiology for applicative researches in medicine and industry. No graduation course in Physics was however established. Pontremoli’s direction abruptly ended in 1928 when he disappeared onboard the “Italia” airship after an accident on the ice-shelf, while he was participating to the scientific polar expedition led by Umberto Nobile.